2002
DOI: 10.1177/03079450094298
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Customers' Emotional Responses to Service Failures on Their Recovery Effort Evaluations and Satisfaction Judgments

Abstract: This study examines the role of customer emotions in the context of service failure and recovery encounters. It investigates how customers' emotional responses to service failures influence their satisfaction judgments after accounting for cognitive antecedents of satisfaction. The study also considers how customers' emotional responses to service failures influence how they evaluate an organization's recovery efforts. The research is conducted by surveying customers about their satisfaction judgments in two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
539
3
16

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 656 publications
(585 citation statements)
references
References 77 publications
27
539
3
16
Order By: Relevance
“…Only 11 items represented by three dimensions were considered as relevant by consumers to describe the emotions felt during a stay at a ski resort. This result corroborates the contextual nature of consumption emotions, as several empirical studies based on the CES in different contexts found a different number of items and dimensions (Ruth et al;, 2002;Smith and Bolton, 2002;Laros and Steenkamp, 2005).…”
Section: Theoretical Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…Only 11 items represented by three dimensions were considered as relevant by consumers to describe the emotions felt during a stay at a ski resort. This result corroborates the contextual nature of consumption emotions, as several empirical studies based on the CES in different contexts found a different number of items and dimensions (Ruth et al;, 2002;Smith and Bolton, 2002;Laros and Steenkamp, 2005).…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…Similarly, emotions mediate the impact of perceived justice on loyalty behaviors (Chebat and Slusarczyk, 2005) and moderate the impact of the providers' recovery efforts on customers' satisfaction (Smith and Bolton, 2002).…”
Section: Emotions' Role In Customers' Experience Evaluationmentioning
confidence: 99%
“…To address these limitations, this study will introduce a considerable number of negative emotions and focus on negative emotions as a pre-complaint construct that is antecedent to complaint behaviour. The present study adopts the view of Smith and Bolton (2002), who contend that negative emotions are provoked by negative critical incidents, which can provoke negative emotions that may lead to complaint action responses.…”
Section: Introductionmentioning
confidence: 99%
“…Smith and Bolton, 2002). More specifically, previous research has assumed consumers either have the ability to form expectation and performance assessments about the service or product (e.g.…”
Section: Introductionmentioning
confidence: 99%